Development of A Presence System for Students Using QR Code Based on Android Application - Mar'atuttahirah Mar'atuttahirah; Mardhiyyah Rafrin; Mahdaniar Mahdaniar; Putri Ayu Maharani (EPI International Journal of Engineering, 2022)
The Department of Information System at Institut Teknologi B.J. Habibie still physically records each student's attendance by having them sign a presence sheet for each course. Due to the ease with which fraudulent signatures can be used to manipulate the traditional system, there may be some issues. Additionally, manual presence recapitulation takes more time and could be less precise and effective. This research aims to develop a prototype of Android-based application of student presence system with QR Code technology in the Department of Information System, Institut Teknologi B.J. Habibie. Following the creation of the presence system prototype, ISO 25010 quality standards were used to evaluate the application. The criteria evaluated are functionality, usability, portability, performance efficiency, and security. The application’s functionality was tested by two system experts by using Guttman Scale and it gained 100% yes answer. The usability was tasted from 30 users rating the application usability through a survey using Likert Scale, it achieved the average percentage of positive answers is 91%. The performance efficiency was classified as grade A by GTmetrix testing site. Similarly, the security system tested by sslabs.com achieved grade A. Furthermore, the portability was tested by using 4 different web browsers for the web version and by installing the application on 4 different smartphones and they showed no errors. Based on the overall assessment result, the Android-based Student Presence System is feasible, efficient, suitable and secure.